Strategi Restructuring Cognitive Dalam Konseling Kelompok CBT Untuk Meningkatkan Kepercayaan Diri Siswa Kelas VIII G di SMP PGRI 1 Buduran Sidoarjo - Oom Linda Rukmana; Kusbandiami; Maghfirotul Lathifah (Universitas Kanjuruhan Malang, 2020)
This study aims to determine the effect of the use of cognitive restructuring strategies in group counseling on class VIII G students' confidence in SMP PGRI 1 BUDURAN SIDOARJO. The research design used was a Pre-Experimental study with a One Group Pretest-Postest Design. The population of class VIII G students at SMP PGRI 1 BUDURAN SIDOARJO was 30 students, then 4 students were taken as research samples using purposive sampling techniques. The selection of this sample was chosen based on the results of students' low self-confidence scores through filling in the scale of student confidence measurement. The results of this study was found that there was no significance changed in the use of cognitive restructuring in counseling group on the confidence of students of class VIII G in SMP PGRI 1 BUDURAN SIDOARJO.